2022
DOI: 10.1111/ijd.16388
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous T‐cell lymphoma following dupilumab use: a systematic review

Abstract: In recent years, studies have associated dupilumab with unmasking or progression of cutaneous T‐cell lymphoma (CTCL). The objective of this study was to synthesize reported cases of CTCL in the setting of dupilumab use. Two independent reviewers conducted a systematic review using PubMed and Embase databases. Twelve studies, of 27 total patients, were included. Dupilumab‐associated CTCL was diagnosed on average 7.8 months following dupilumab initiation. Of reports that included body surface area (BSA), 100% ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Most patients presenting with CTCL triggered by dupilumab are diagnosed with more advanced disease and it is thought that dupilumab causes rapid worsening in CTCL via immune dysregulation with a Th2-dominant immune profile. 5 To our knowledge, AITL occurring in the setting of dupilumab therapy has not been previously reported. Notably, AITL is a significantly more aggressive disease compared to CTCL.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Most patients presenting with CTCL triggered by dupilumab are diagnosed with more advanced disease and it is thought that dupilumab causes rapid worsening in CTCL via immune dysregulation with a Th2-dominant immune profile. 5 To our knowledge, AITL occurring in the setting of dupilumab therapy has not been previously reported. Notably, AITL is a significantly more aggressive disease compared to CTCL.…”
Section: Discussionmentioning
confidence: 79%
“…The overall 5-year survival rate of AITL is 33% whereas 5-year survival for mycosis fungoides is 88%. 1 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…To date, 12 studies including a total of 27 patients report the development of CTCL after dupilumab treatment for an initial diagnosis other than CTCL, or demonstrate exacerbation of CTCL with dupilumab [ 14 ]. Our case demonstrates such a conundrum, where several outside biopsies were performed showing spongiotic and lichenoid patterns.…”
Section: Discussionmentioning
confidence: 99%
“…For a complete review of demographic and histologic findings of recently reported dupilumab-associated CTCL cases, please refer to the systematic review [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation